2012
DOI: 10.4103/0019-5545.102424
|View full text |Cite
|
Sign up to set email alerts
|

Role of antioxidants in generalised anxiety disorder and depression

Abstract: Background:Anxiety and depression form commonest stress-induced psychiatric disorders. To combat the biochemical changes which occur as a result of stress, there is antioxidant defence in the biological system. Secondary defence is by the nonenzymatic antioxidants like vitamins E (alphatocopherol), C (ascorbic acid), and β-carotene. Therefore, the authors interest was aroused to examine the status of these antioxidants in the biological system of patients suffering from stress-induced psychiatric disorders.Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
2
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 10 publications
8
92
2
10
Order By: Relevance
“…The increased oxidative stress maintained by different antioxidant system (ascorbic acid, vitamin-E, SOD and so forth) and this antioxidants status altered in different uncontrolled disease condition [29][30][31][32]. Ascorbic acid, an antioxidant, has negative correlation with the major depression is a finding well-established [33]. Even in the present scenario ascorbic acid has been found to be effective in the mouse model of depression [34].…”
Section: Discussionmentioning
confidence: 66%
“…The increased oxidative stress maintained by different antioxidant system (ascorbic acid, vitamin-E, SOD and so forth) and this antioxidants status altered in different uncontrolled disease condition [29][30][31][32]. Ascorbic acid, an antioxidant, has negative correlation with the major depression is a finding well-established [33]. Even in the present scenario ascorbic acid has been found to be effective in the mouse model of depression [34].…”
Section: Discussionmentioning
confidence: 66%
“…Oral supplementation of vitamin C with antipsychotic reverses AA levels, reduces oxidative stress, and improves BPRS score, hence both the drugs in combination can be used in the treatment of schizophrenia [225]. The findings of another study suggest that antioxidant supplement therapy as an adjuvant therapy is useful in patients with stressinduced psychiatric disorders [226]. There are also reports advocating beneficial effect of vitamin C in neurodegenerative disorders including Alzheimer's disease.…”
Section: Vitamin C and Neurodegenerative Disordersmentioning
confidence: 99%
“…Polyphenols, flavonoids, specific foods and diets rich in antioxidants have been shown to improve antioxidant status and have anxiolytic effects. 7,9 Plant extracts, which contain phenolic constituents mainly flavonoids, have shown beneficial effects on mental health. Extracts of plants like Pulsatilla nigricans, 40 Tephrosia purpuria, 41 Coriandrum sativum, 42 Gastrodia elata, 43 Citrus paradisi 44 contain flavonoids and possess antianxiety activity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have revealed that antioxidants have a key role as an adju-vant therapy in patients with generalized anxiety disorder and depression. 7 Flavonoids are reported to be potent antioxidants. [8][9][10] Many plants containing flavonoids are reported to possess anxiolytic potential.…”
Section: Introductionmentioning
confidence: 99%